Resposta produtiva do feijoeiro comum a diferentes manejos de irrigação - De Faria, Manoel Teixeira [UNESP] (2012)
The objective of this work was to analyze the most appropriate management to achieve higher productivity for carioca beans (phaseolus vulgaris) and pearll cultivar. The research was developed in the Demonstrative and Experimental Area of Irrigation (ADEI) of FCAV/UNESP, Campus of Jaboticabal, SP. Four treatments were used: T1- irrigation with base in ETo estimated by the method of Class A pan; T2- irrigations based on the readings of tensiometers installed at 0,20 m and 0,40 m of depth; T3- irrigations carried out with base in ETo estimated by the method of Penman-Monteith and T4- witness. The results were submitted to analysis of variance. To compare the averages the test Turkey was used at 5% of probability. The treatment T3 had smaller applied water depth than the treatments T1 and T2, and also smaller productivity. The conclusion is that the treatments irrigated with larger frequency showed higher production of grains.